(untitled) (International Journal of Nursing Education, 2019)
The foundation of good research and of good decision making in evidence based practice nursing is the trustworthiness of data. The significant qualities in the decision making process in tool construction are reliability and validity. In India, epidemiology and behavioural disorder of children is not studied on form. It is the right time to assess on obstruction that affects normal development of children. The authors described the sequential process of development of attitude scale to assess behaviour and emotional problem of children among primary school teachers. It is a self administered 42 items Likert scale that quantifies 6 aspects of attitude of primary school teachers. The attitude aspects covered are academic Performance, rules and regulations, communication and distractibility, disobedience, aggression and peculiar behaviour. The sequential steps carried out in development of tool are extensive literature review, item construction, item analysis, validity, reliability, and piloting the tool. Tool was submitted for content validity to seven experts and content validity ratio was one. Item analysis was computed. Test retest reliability was computed and item to item correlation computed using chronbach’s alpha. The r value was 0.82 which indicate that the tool was highly reliable.